Bioelectrochemical systems (BESs) towards conversion of carbon monoxide/syngas: A mini-review - Barbosa, Sónia G. (2021)
Microbial conversion of carbon monoxide (CO)/syngas has been extensively investigated. The microbial conversion of CO/syngas offers numerous advantages over chemically catalyzed processes e.g. the specificity of the biocatalysts, the operation at ambient conditions and high conversion efficiencies. Bioelectrochemical systems (BESs) exploit the capacity of electrochemically active bacteria (EAB) to use insoluble electron acceptors or donors to produce electricity or added-value compounds. Electricity production from different organic sources in BESs has been broadly demonstrated, whereas electricity production from CO/syngas has been very little reported. Acetate oxidation by a consortium of carboxydotrophic and CO-tolerant EAB has been suggested to be the main pathway responsible for indirect electricity generation from CO/syngas. Although electricity production in BESs from several organic sources has been widely investigated, the interest on BESs research is currently moving to the production of added-value compounds by electro-fermentation (EF) processes. EF allows to modify redox balances by the use of electric circuits to fine tune metabolic pathways towards obtaining products with high economic value. Although EF has been widely studied, the potential of use CO-rich gas streams as substrate has been under explored. This review presents and discusses current advances on microbial conversion of CO/syngas in BESs.